DAYA TARIK MASYARAKAT UNTUK BEKERJA DI SEKTOR TRANSPORTASI ONLINE (STUDI KASUS BANDA ACEH) - Randha Prasetyo; Eddy Gunawan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to see the attractiveness of the community to work the online transportation sector in Banda Aceh City. By using income, education, freedom in work, and employment opportunities. The analysis model in this study is multiple linear regression using primary data. The results showed that the effect of employment opportunities on attractiveness to work in the online transportation sector was positively related, with a significant value of 0.034 0.05 and a T-count value of 2.145 T-table 1.988 so it can be concluded that the hypothesis was accepted. The effect of freedom in work on the attractiveness of working in the online transportation sector is negatively related, it is known that the value is not significant at 0.089 0.005 and the T-count value is -1.718 T-table 1.988 so it can be concluded that the hypothesis is rejected. The effect of income on attractiveness for working in the online transportation sector is negatively related, it is known that the value is not significant is 0.224 0.05 and the calculated T value is 1.224 T-table 1.988 so it can be concluded that the hypothesis is rejected. For further research, it is suggested that it can add unemployment variables and the research carried out to focus more on Indonesia.Keywords: Online Transportation, Income, and employment opportunity